Impacts of Climate Change on Biodiversity Resources & Forest Ecosystems - Thakur, Ram B; Phulara, Nirmala K (The Initiation, 2010)
Climate Change is a key challenge of biodiversity conservation. Impacts of climate change are significant on physiology, phenology and distribution of species, seasonal biological phenomenon of floral and faunal species, animal life cycle, migratory birds and wild animals, mountain ecosystems, wild animals' habitat as well as coral reefs habitat. Moreover, impacts of climate change are also on preservation of wild animals and plants in protected areas, shifting of bio-climatic zones, endangered & vulnerable flora and fauna and biodiversity hotspots. The change in hydrological cycle due to global warming affect on river run-off, accelerate water-related hazards and affect also on agriculture, vegetation, forests, biodiversity and health. Key Words: Carbon sequestration, Seasonal biological phenomenon, Shifting bio-climatic zones, Biodiversity hotspots DOI: 10.3126/init.v3i0.2499 The Initiation Vol.3 2009 p.86-96